Pop Up Book Media to Improve Student Learning Outcomes in Thematic Learning Theme of Objects Around Me in Class III State Primary School 064986 Medan - Yanisyah Intan Sari Siregar; Samsul Bahri (PT Inovasi Pratama Internasional, 2023)
This research aims to determine the effectiveness of applying pop up book media in improving student learning outcomes in thematic learning with the theme